CHANGES IN BIOCHEMICAL PARAMETERS OF BLOOD SERUM AND GINGIVAL HOMOGENATES WITH EXPERIMENTAL GINGIVITIS - Malko, N.V.; Hasiuk, P.A.; Ivanchyshyn, V.V.; Hasiuk, N.V. (World of Medicine and Biology, 2017)
Inflammatory periodontal diseases is an urgent problem not only in dentistry, but also in general medicine, due to their high prevalence and negative effects on a human body causing significant economic consequences. As a result, the bioregulation of biochemical processes is often damaged, due to it, at a certain level of damage, different diseases, including dental ones, occur and develop. Moreover, the study of the impact of the combined action of xenobiotics on biochemical tissue indicators of a growing up human body, the development of new means of correction, which are based on inhibition of proteases, hydrolases, kinin system, normalization of tissue penetration, enhancing the action of protective factors of a human body, ensuring the sustainability of periodontal tissues to the negative influence of environmental agents, are important and poorly understood issues. Research purpose – to study the biochemical parameters of blood serum and homogenates of the gums in experimental animals with gingivitis caused by the combined action of heavy metals and deficiency of fluorine and iodine. Consequently, experimental studies have convincingly demonstrated that in experimental gingivitis under the influence of the adverse environmental factors the levels of inflammatory markers ‒ elastase and urease, as well as the indices of the protease-inhibitory system increased.